Reducing Resistance to Organizational Change by Promoting Change Leadership: A Study of The MBKM Curriculum Implementation in Higher Educational Institutions - Mujib, Miftachul; Fahmi Wardhani, Masitha; Kurniawan, Rudi (Publisher Cv. Inara, 2023)
The purpose of this study is to investigate how change information affects resistance to organizational change in the context of MBKM Curriculum implementation. We also examine the moderating role of change leadership on the effect of change information on resistance to change in the MBKM Curriculum implementation. The population of this research is all lecturers in Indonesia. The number of samples used was 156 obtained by random sampling technique. Data processing was carried out using the SEM-PLS methode by the Warp-PLS 6.0 application. The results show that change information has a negative effect on resistance to changes in the MBKM Curriculum. Change leadership also has a negative moderating role in the relationship between change information and resistance to changes in the MBKM Curriculum. The results of this study enrich the literature on organizational change management in particular by clarifying the antecedents of resistance to organizational change, namely change information. This research shows the importance of higher education institutional leaders to implement change-oriented leadership in overseeing the implementation of changes to the MBKM Curriculum.